âYou Donât Have To Be Innovative In the Creative Industriesâ A Study of Entrepreneurial Orientation and Social Capital in Creative Industries - Wardani, Dewi Kusuma (Sebelas Maret University, 2016)
Competitiveness and performance of businesses in the creative industry have the disadvantage of resource management and development and entrepreneurial policies. Creative industries covering the fashion industry, design, and craft are industries that expected to be able to competewith the establishment of the Asian Economic Community (AEC) by 2015. To improve the capability to compete in the regionally and globally, internal capabilities such as Entrepreneurial Orientation (EO) and social capitals (SC) of companies in the creative industry need to improve. Entrepreneurial Orientation has been the focus of many researchers and contributed significantly to the development of entrepreneurship literature over the decades. This fact supported by empirically significantfindings contributedby various researchersin the literature. However, up to the date there are many debates and require more research, specifically in the robustness of the dimensions within creative industries. The current research using Mixed Methods analyses tested the EO and SC model to 60 entrepreneurs in the creative industries within specific areasof fashion, design and crafting in Central Java regions. Findings suggested that in the creative industries, EO varied to those companies in manufacturing and technology industries. Â The current research contributed to the literatureby (1) modelling the EO in the creative industry, (2) confirming previous research findings on Entrepreneurship Orientation, (3) suggesting the source of competitive advantage in this industry, (4) social capital not adopted scientifically.However, these findings should require more extensive research and tested across regions. Hence, the directions for future research are implied in the research limitations section.